Repeatability of associations between analytical methods of adaptability, stability, and productivity in soybean - Leomar Guilherme Woyann; Anderson Simionato Milioli; Antonio Henrique Bozi; Samuel Cristian Dalló; Gilvani Matei; Lindolfo Storck; Giovani Benin (Pesquisa Agropecuária Brasileira, 2018)
Abstract: The objective of this work was to evaluate the association between estimates of adaptability, stability, and productivity in soybean (Glycine max), and to estimate the repeatability coefficient of these associations between years. A total of 22 genotypes were evaluated in 27 environments in the 2012/2013 crop season and in 19 environments in 2013/2014. In the next crop seasons, 28 genotypes were evaluated in 26 environments, in 2014/2015, and in 25 environments in 2015/2016, totalizing 97 trials. Fourteen methods were evaluated; Spearman correlation coefficients were obtained for the parameters of stability, adaptability, and productivity; and the repeatability coefficients, as well as the minimum number of required environments for a coefficient of determination of 80 and 90%, were calculated. The minimum number of environments required to estimate the degree of association between the parameters was low (seven sites). The methods of Eberhart & Russell and GGE biplot are essential in the evaluation of productivity, adaptability, and stability in soybean because they are able to encompass these aspects using a minimum set of methods. The methods of Annicchiarico (AN), Silva & Barreto (SB), Cruz (CR), and Storck & Vencovsky (SV) can be used to generate complementary information, such as: stability for general, favorable, and unfavorable environments (AN); adaptability in favorable and unfavorable environments (SB, CR, and SV); and average productivity in all environments and in favorable or unfavorable environments (SV).